Symbiont–host relationships in chemosynthetic mussels: A comprehensive lipid biomarker study - Kellermann, M Y; Schubotz, F; Elvert, M; Lipp, J S; Birgel, D; Prieto-Mollar, X; Dubilier, N; Hinrichs, K -U (Organic Geochemistry, 2012)
Symbiosis with chemosynthetic microorganisms allows invertebrates from hydrothermal vents and cold seeps, such as mussels, snails and tubeworms, to gain nutrition independently of organic input from photosynthetic communities. Lipid biomarkers and their compound specific stable carbon isotopes ($δ$13C) have greatly aided the elucidation of chemosynthetic symbiosis. Due to recent methodological advances in liquid chromatography it is now possible to obtain a more holistic view of lipid biomarkers, including the analysis of intact polar membrane lipids (IPLs) and bacteriohopanepolyols (BHPs). This study provides an extensive examination of polar and apolar lipids in combination with stable carbon isotope analysis of three Bathymodiolus mussels (Bathymodiolus childressi, Bathymodiolus cf. thermophilus, Bathymodiolus brooksi) hosting different types of bacterial symbiont (methane-oxidizing, sulfur-oxidizing and a dual symbiosis with methane- and sulfur-oxidizing symbionts, respectively). We propose that IPLs with C16:1 acyl side chains, and phosphatidylglycerol (PG), diphosphatidylglycerol (DPG) and phosphatidylethanolamine (PE) head groups, which were only detected in the gill tissue, can be used as symbiont-characteristic biomarkers. These putative symbiont-specific IPLs provide the opportunity to detect and quantify the methanotrophic and thiotrophic symbionts within the gill tissue. Additional characteristic markers for methanotrophic symbionts were found in B. childressi and B. brooksi, including the BHP derivatives aminotriol and aminotetrol, 4-methyl sterols and diagnostic fatty acids (FAs), such as C16:1$ømega$9, C16:1$ømega$8, and C18:1$ømega$8. In general, the $δ$13C values of FAs, alcohols and BHP-derived hopanols were in accordance with carbon assimilation pathways of the respective methanotrophic or thiotrophic symbionts in all three Bathymodiolus mussels. Differences in BHP distribution as well as $δ$13C values in the two mussels hosting a methanotrophic symbiont may indicate the presence of different methanotrophic symbionts and/or changes in the nutritional status. In all three mussel species the $δ$13C values of lipid biomarkers assigned to the symbionts were similar to those of the hosts, indicating the importance of the bacterial symbionts as the main carbon source for the mussel tissue.
Keywords: HOV Alvin (Human Occupied Vehicle)